The Effect of English News Video on Students’ Speaking Skill - Hidayati, Anni Nurul (Journal of Language Intelligence and Culture, 2020)
The aim of this research is: (1) to know the implementation of the technique of making an English news video to improve students’ Speaking skill, (2) to know the ability of the students non English in improving speaking skill. The research was conducted at students majoring Islamic Communications and Broadcasting of IAIN Surakarta. The researcher used qualitative research method to find out the improvement of the students’ speaking skill. The researcher collected the data through observation, interview, and documentation. The researcher obtained the data during teaching and learning processes. Based on the research that has been done, it can be concluded that: (1) the implementation of making an English News Video gives advantages for students’ in improving speaking skill, especially on communications and broadcasting field; (2) the non-English students got a lot of communications and broadcasting vocabulary, become more active and fearless in making mistake when showing their ideas after doing this research.